PERSEPSI MAHASISWA TENTANG PEMBELAJARAN ONLINE DI MASA PANDEMI COVID-19 - Zulika Hapsari, Famela Meilidia; Ulfah, Maria; Barella, Yusawinur (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This study aimed to gather the perception of students regarding online learning during the COVID-19 pandemic, on the aspect of the existence of teaching lecturers and interactions between lecturers and students. This study used a qualitative descriptive research method. The sources of data were observation data, students' interview results, and documentation of online lecture activities. The results showed that the existence of teaching lecturers in online learning was going well. This was proven by the lecturer providing planning of teaching materials according to the learning objectives but not providing the lecture syllabus, explaining the lecture contract to students at the beginning of the lecture, and providing the lecture schedule which was carried out by the lecturer being present on time. The results of research on the interaction between lecturers and students showed positive results. However, there were also things that needed to be improved, such as the internet network.